2013
DOI: 10.1071/mu12082
|View full text |Cite
|
Sign up to set email alerts
|

The form and function of duets and choruses in Red-backed Fairy-wrens

Abstract: In many avian species, both members of a pair or all members of a breeding group sing, often in duets or choruses. Previous studies indicate that duets often function in territorial defence. However, other potential functions, such as acoustic mate-guarding, need further study, because most species that have been studied have low or unknown rates of extrapair paternity (EPP) and theoretical models predict species with moderate rates of EPP will guard more than those with very low or high rates. We conducted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…In red-backed fairy-wrens, there is support for territory establishment and defence [21,22], but the results presented here suggest that strong duetting response is also associated with increased paternity assurance. This pattern has been inferred previously from behavioural evidence or life-history trends [27][28][29], but this study is, we believe, the first to demonstrate a clear link based on within-population variance in duetting and genetic paternity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In red-backed fairy-wrens, there is support for territory establishment and defence [21,22], but the results presented here suggest that strong duetting response is also associated with increased paternity assurance. This pattern has been inferred previously from behavioural evidence or life-history trends [27][28][29], but this study is, we believe, the first to demonstrate a clear link based on within-population variance in duetting and genetic paternity.…”
Section: Discussionmentioning
confidence: 55%
“…12: 20151025 duets that were joined by males, as would be predicted by this hypothesis. Nonetheless, previous work on another population of red-backed fairy-wrens failed to demonstrate acoustic mate guarding [21,22]. Another possibility is that duetting is a general 'keep out' signal produced by the pair to prevent usurpation of a partner or pair bond position [23].…”
Section: Discussionmentioning
confidence: 96%
“…More detailed work on other forest-dwelling Neotropical wrens using radiotracking (Logue, 2007a) and passive acoustic location of singing individuals (Mennill and Vehrencamp, 2008) has shown that duet responses are often given by individuals more than 10 m from their partner, with the initiator then moving closer to its partner, suggesting that duetting functions cooperatively in maintaining contact and pair cohesion. Banded wrens and other species that duet when partners are not perched next to one another thus contrast with duetting species that sing together while perched within a meter or two of one another (for examples, see Short and Horne, 1982;Hall and Magrath, 2000;Hall and Peters, 2008;Dowling and Webster, 2013).…”
Section: Coordination With Partnermentioning
confidence: 99%
“…Identifying the ecological and life-history correlates of female song requires detailed study of song, particularly in species that diverged closest to the ancestral node (Odom et al, 2014). At present, little is known about female song in other early diverging species, with the exception of the Maluridae (Cooney and Cockburn, 1995;Hall and Peters, 2008;ColombelliNégrel et al, 2010;Dowling and Webster, 2013;Cain et al, 2015). Therefore, it is not yet clear what aspects of song in lyrebirds have been retained since their ancestor diverged from the main branch of the oscines, and what features have since evolved.…”
Section: General Implications For Elaborate Vocalizations In Female Smentioning
confidence: 99%